Anti-Inflammatory Test Macaranga gigantea with Interleukin Inhibitor approach In Silico - samsul hadi; kunti nastiti (Institute of Computer Science (IOCS), 2022)
Inflammation is condition inflammation accompanied by pain and fever . _ In general drug anti-inflammatory work with hinder enzyme cyclooxygenase , both COX-1 and COX-2, which play a role in synthesize inflammatory mediators such as prostaglandins and thromboxane . Various study developed for look for agent more therapy effective and have more risk low good symptom inflammation I or consequence period long from disease inflammation chronic . One of the approach taken is develop IL1β inhibitors. Method used is compound screening active using in silico. Docking software used in study this is autodock 4.2 and visualization interaction using discovery studio , materials used in study this is the compounds contained in M. gigantea. Result of research this is the value of delta G is negative below -4 kcal / mol, so reaction yanga occur between the ligand and the protein will walk spontaneous . Conclusion in study this obtained four ligands with lowest G value that is glycasperin A; broussoflavonol F; 5,7,3 ',4'-Tetrahydroxy-3-methoxy-8,5'-diprenylflavone; meliternatin .